The Effect of TNF-α and FIB-4 Score on Diastolic Dysfunction in Child Pugh C Liver Cirrhosis - Karim, Muhammad Yusuf; Pramana, Triyanta Yuli; Sulastomo, Heru; Nurudhin, Arief; Pamungkasari, Eti Poncorini (Gema Lingkungan Kesehatan, 2025)
Liver cirrhosis is a major global health concern, often complicated by cardiac dysfunction such as diastolic heart failure. Tumor necrosis factor-alpha (TNF-α) and FIB-4 score are widely used biomarkers in cirrhotic patients, but their predictive value for cardiac complications remains unclear. To determine the effect of TNF-α and FIB-4 scores on the severity of diastolic dysfunction in patients with Child-Pugh C liver cirrhosis. This analytical cross-sectional study included 40 Child-Pugh C cirrhotic patients. Serum TNF-α levels were measured using ELISA. Diastolic function was evaluated using echocardiography. Ordinal logistic regression was used to analyze the association between TNF-α, FIB-4, and diastolic dysfunction grades. The majority of participants had moderate (65.0%) or severe (35.0%) chronic inflammation based on TNF-α levels, with a median TNF-α of 45.52 pg/mL. Significant liver fibrosis (FIB-4 >3.25) was observed in 82.5% of participants. Grade I diastolic dysfunction was the most prevalent (52.5%). TNF-α levels were significantly associated with the degree of diastolic dysfunction (p=0.042), whereas FIB-4 scores showed no significant correlation (p=0.533). Elevated TNF-α is strongly associated with worsening diastolic dysfunction in Child-Pugh C cirrhosis, suggesting its role in systemic inflammation and myocardial injury. In contrast, the FIB-4 index may not reflect cardiac involvement in advanced cirrhosis. TNF-α may serve as a potential biomarker for cardiovascular risk stratification in cirrhotic patients, supporting early intervention and integrated care approaches.